Parents Left Behind: Does Migration of Adult Children indicate Prevalence of Depression? - Mohan , Anu; M.L., Parvathy (Journal of Social Work Education and Practice, 2023)
The out-migration of young adults from the household has contributed to the separation of many families and also resulted in children and older family members being ‘left behind’. As per the global trend approximate number of international and internal migrants are 232 million and 740 million respectively. Middle adulthood is a period of stress and storm. Parents who are staying alone may have reduced psychological health due to less opportunities for social gathering, isolation and anxiety of being alone.This study focuses on the depression and life satisfaction of parents left behind. For the present study 60 Parents from the Idukki district whose children have migrated were selected using purposive sampling and administered with becks depression inventory and satisfaction with life scale. The study shows a significant relationship (p=.000) between depression and life satisfaction of parents with migrated children. It gives a reflection on the coping strategies used by parents. The out-migration of young adults from the household especially rural people for better opportunities to cities has contributed to the separation of many families and also resulted in children and older family members being ‘left behind’. The results can be evaluated to administer an intervention package among such parents through group work and casework sessions. The study has implications for Social work research and practice.
Keywords: life satisfaction; depression; parents left behind; coping strategies